Investigation of SARS-CoV-2 release in fecal specimens of discharge COVID-19 patients - Koparan, Arzu; Dede, Sureyya; Isiksacan, Nilgun; Yesilbag, Zuhal; Karakus, Emine (WALTER DE GRUYTER GMBH, 2024)
Objectives The presence of live SARS-CoV-2 viruses in the fecal specimens and the positive results for SARS-CoV-2 RNA in gastrointestinal samples after respiratory specimens had become negative indicate that there may be a risk of transmission of the disease not only through the respiratory tract but also through the fecal-oral route. The study aim is to determine the time period that the SARS-CoV-2 virus remains in the fecal specimens of discharged COVID-19 patients to reveal the time interval in which the risk of transmission continues.Methods In 65 patients hospitalized with a COVID-19 diagnosis, the viral RNA was isolated from the supernatant of the stool sample using CVXTM viral RNA extraction kit. The extracted RNAs from the stool samples were detected using a commercial RT-PCR method.Results Positive results were obtained in the stool samples in eight of sixty-five patients and the presence of SARS-CoV-2 in these patients was detected for up to three weeks.Conclusions By determining the residence time of SARS-CoV-2 virus in stool samples of discharged COVID-19 patients, the time interval during which the possibility of transmission risk continues has been revealed. The findings of the study could prove beneficial in comprehending the risks of transmission and translating them into preventative measures.
Keywords: COVID-19 disease; SARS-CoV-2; stool sample; fecal-oral transmission; patient; Biochemistry & Molecular Biology